To solve the system:
-3x - 4y = -18
-2x + 4y = 8
We can use the method of elimination. Adding both equations eliminates the term with "y":
(-3x - 4y) + (-2x + 4y) = (-18) + 8
-3x - 2x - 4y + 4y = -10
-5x = -10
x = -10 / -5
x = 2
Now that we have the value for x, we can substitute it into one of the original equations to solve for y. Let's use the second equation:
-2x + 4y = 8
-2(2) + 4y = 8
-4 + 4y = 8
4y = 8 + 4
4y = 12
y = 12 / 4
y = 3
Therefore, the solution to the system of equations is (x, y) = (2, 3).
solve the system:
-3x-4y=-18
-2x+4y=8
put your answers in ordered pair form: (x,y). show your work.
1 answer